MATHEMATICAL MODELS FOR RESEARCH INNOVATION - F.Z MEHDI (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
Methods for quantifying innovation made it possible to assess the level of development of innovation activities in countries and to determine their comparative indices for various determinants of innovation and ratings. But this is not the only, not even the main, benefit of calibrating innovation factors and innovation in general. The possibility of numerical reflection of innovative factors makes it possible to apply quantitative methods, including methods of statistics and economic and mathematical modeling. This is very important for making political decisions, both at the macro and micro levels, since this opportunity allows us to assess the degree of influence of various factors on innovative activity, as well as the impact of innovative development on the socio-economic well-being of the population and the company. Therefore, in the scientific literature there are many publications on research in these areas, the analysis of which is of interest for conducting research on Azerbaijan. Consider some of these typical studies.